Association of Inflammatory Periapical Lesions with Maxillary Sinus Abnormalities: a Retrospective Cone-Beam Computed Tomography Study - Saeede Zadsirjan; Mahnaz Sheikhi; Ali Dakhilalian; Mojgan Feli (Shiraz University of Medical Sciences, 2021)
Statement of the Problem: Odontogenic infections such as periapical lesions (PLs) can cause changes in the adjacent tissues. Infection of the maxillary posterior teeth can be easily transmitted to the maxillary sinus and cause changes in the maxillary sinus mucosa. Cone-beam computed tomography (CBCT) has high accuracy and sensitivity for detection of odontogenic lesions and is efficient for maxillary sinus assessment. Purpose: This study aimed to assess the maxillary sinuses for abnormalities such as mucosal thickening, polyps, and periostitis, and evaluate the periapical status of maxillary posterior teeth considering the presence of PLs, their size and distance from the sinus floor by evaluating CBCT images. Materials and Method: This retrospective, cross-sectional study evaluated the CBCT scans of 143 patients, depicting the posterior maxilla with at least one premolar or molar tooth present in this region. Sinus abnormalities (mucosal thickening, sinus polyps, and periostitis) and presence/ absence of PLs, its size, and its distance from the sinus floor were all assessed on CBCT scans. Data were analyzed using the Chi-square test in SPSS version 21 (a= 0.05). Results: PLs were observed in 31.2% of the cases. In presence of PLs, mucosal thickening was noted in 56.8%, sinus polyps in 29.6% and periostitis in 1.3% of the maxillary sinuses. All teeth with a CBCT periapical index (CBCTPAI) score of 5 were associated with sinus abnormalities; there was neither correlation between the sizes of lesions, nor their distance from the sinus floor with sinus abnormalities (p> 0.05). Conclusion: PLs in the posterior maxilla have a direct correlation with the maxillary sinus abnormalities. However, the size or distance of PLs from the sinus floor had no significant effect on the frequency of sinus abnormalities.